Water use of deciduous and evergreen tree nut crops : a case study using pecans and macadamias - Taylor, Nicolette Jane (University of Pretoria, 2018)
Adequate water supply is crucial for optimal fruit production, with the consequence that the vast majority of orchards are dependent on irrigation, particularly in arid and semi-arid climates where rainfall is low and erratic. Consequently, irrigation water management and planning, through accurate quantification of crop water use or evapotranspiration (ET, composed by soil evaporation – Es and transpiration - T), becomes a vital factor for maximization of orchard profitability. The ET of fruit tree species is highly variable and is affected by several factors including changes in climate and orchard management practices. Direct measurements of crop ET are practically impossible under all possible conditions, and thus crop modelling is required to estimate water use for different scenarios. The selection of an appropriate modelling approach to address a specific situation requires an understanding of the regulation of T and Es, as affected by the variability in the driving factors. This study investigated the regulation of water use in two tree nut species, with contrasting growth habits (pecans a deciduous species and macadamias an evergreen species) in order to identify the most suitable crop modelling approaches to estimate the water use of these crops, for improved irrigation scheduling and planning. Field trials were conducted for two to three consecutive growing seasons in a 7-year-old pecan orchard at Hatfield, a 37-year-old pecan orchard at Cullinan and a 6-year-old macadamia orchard at White River. Measurements included T (heat ratio method), crop ET (eddy covariance technique), Es (micro-lysimeters), weather variables (automatic weather stations installed on-site), changes in soil water content (TDR100 system) and solar irradiance transmittance through the canopy (Delta-T tube solarimeters). Field measurements were used to investigate the environmental control of T using a quantile regression approach, as well as for parameterization and validation of the following modelling approaches: FAO-56 single and dual crop coefficient (Kc), radiation interception by the canopy and canopy conductance models. Transpiration normalised for canopy size was well-coupled to the atmosphere in both pecans and macadamias, and primarily driven by vapour pressure deficit (VPD), with T rates of both crops decreasing considerably once a threshold VPD had been reached (1.4 kPa for pecans and 1.2 kPa for macadamias), indicating the presence of a strong stomatal control during these periods. Despite such similarity in their process of water use, pecans and macadamias showed slightly different mechanisms of crop water use at relatively lower levels of VPD, with T being primarily demand-limited in pecans and supply-limited in macadamias. The common presence of strong stomatal control in both crops is typically associated with high coupling of T to the atmosphere in tall deciduous and evergreen perennial tree crops, while their slightly distinct crop water use patterns are likely related to their varying growth habits. Daily T of pecans and macadamias was accurately predicted with a canopy conductance model parameterized for each crop, while daily Es beneath the canopy was accurately obtained with the FAO-56 dual Kc model. These daily estimates could contribute greatly to improved irrigation scheduling of these orchard crops. While daily predictions of T and Es required the use of relatively more complex modelling approaches, monthly estimates of ET were accurately obtained for these crops using simple, single Kc modelling approaches, which can significantly contribute to improved irrigation planning and water resources management for the respective orchard crops. Monthly ET of pecans was, however, more accurately predicted with a crop-specific single Kc model, while a generic model using crop-specific Kc values was sufficient to provide accurate predictions of monthly ET of macadamias.